Role of recently evolved miRNA regulation of sunflower HaWRKY6 in response to temperature damage - Giacomelli, Jorge Ignacio (2012)
MicroRNAs (miRNAs) are small 21-nucleotide RNAs that post-transcriptionally regulate gene expression. MiR396 controls leaf development by targeting GRF and bHLH transcription factors in Arabidopsis. WRKY transcription factors, unique to plants, have been identified as mediating varied stress responses. The sunflower (Helianthus annuus) HaWRKY6 is a particularly divergent WRKY gene exhibiting a putative target site for the miR396. A possible post-transcriptional regulation of HaWRKY6 by miR396 was investigated. Here, we used expression analyses, performed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and northern blots together with computational approaches to establish the regulatory interaction between HaWRKY6 and the identified sunflower miR396. Arabidopsis plants expressing a mi396-resistant version of HaWRKY6 confirmed the miRNA-dependency of the HaWRKY6 silencing. Sunflower plants exposed to high temperatures or salicylic acid presented opposite expression of HaWRKY6 and miR396. Experiments using the wildtype and miRNA-resistant versions of HaWRKY6 showed altered stress responses. Our results showed a role of the recently evolved miR396 regulation of HaWRKY6 during early responses to high temperature. Our study reveals how a miRNA that normally regulates development has been recruited for high-temperature protection in sunflower, a plant particularly well adapted to this type of stress.